Humanitarian logistics cross-sector cooperation in disaster relief management - Cozzolino, Andrea 1948- (SpringerBriefs in business, 2012)
The main aim of this study is exploring in depth the partnership between profit and non-profit in emergency relief operations, with specific attention to the cross-learning potential for both the logistics service provider (profit) and the humanitarian organization (non-profit).